STRUCTURAL AND FUNCTIONAL-EFFECTS OF APOLAR MUTATIONS OF THE DISTAL VALINE IN MYOGLOBIN - Quillin, M. L.; Li, T. S.; Olson, J. S.; Phillips, G. N.; Dou, Y.; Ikedasaito, M.; Regan, R.; Carlson, M.; Gibson, Q. H.; Li, H. Y.; Elber, R.; 李海燕 (1995)
High-resolution structures of the aquomet, deoxy: and CO forms of Ala68, Ile68, Leu68, and Phe68 sperm whale myoglobins have been determined by X-ray crystallography. These 12 new structures, plus those of wild-type myoglobin, have been used to interpret the effects of mutations at position 68 and the effects of cobalt substitution on the kinetics of O-2, CO, and NO binding. Molecular dynamics simulations based on crystal structures have provided information about the time-dependent behavior of photolyzed ligands for comparison with picosecond geminate recombination studies. The Val68-->Ala mutation has little effect on the structure and function of myoglobin. In Ala68 deoxymyoglobin, as in the wild-type protein, a water molecule hydrogen-bonded to the N-epsilon atom of the distal histidine restricts ligand binding and appears to be more important in regulating the function of myoglobin than direct steric interactions between the Ligand and the C-gamma atoms of the native valine side-chain. This distal pocket water molecule is displaced by the larger side-chains at position 68 in the crystal structures of Leu68 and Ile68 deoxymyoglobins. The Leu68 side-chain can rotate about its C-alpha-C-beta and C-beta-C-gamma bonds to better accommodate bound ligands, resulting in net increases in overall association rate constants and affinities due to the absence of the distal pocket water molecule. However, the flexibility of Leu68 makes simulation of picosecond NO recombination difficult since multiple starting conformations are possible. In the case of Ile68, rotation of the substituted side-chain is restricted due to branching at the beta carbon, and as a result, the delta methyl group is located close to the iron atom in both the deoxy and liganded structures. The favorable effect of displacing the distal pocket water molecule is offset by direct steric hindrance between the bound ligand and the terminal carbon atom of the isoleucine side-chain, resulting in net decreases in affinity for all three ligands and inhibition of geminate recombination which is reproduced in the molecular dynamics simulations. In Phe68 myoglobin, the benzyl side-chain is pointed away from the ligand binding site, occupying a region in the back of the distal pocket. As in wild-type and Ala68 myoglobins, a well-defined water molecule is found hydrogen bonded to the distal histidine in Phe68 deoxymyoglobin. This water molecule, in combination with the large size of the benzyl side-chain, markedly reduces the speed and extent of ligand movement into the distal pocket. Ligand movement away from the iron atom is also reduced dramatically by the Phe68 side-chain, causing large and rapid geminate recombination phases for all Ligands.